Labour and the decolonization struggle in Trinidad and Tobago - Teelucksingh, Jerome (Cambridge imperial and post-colonial studies series., 2014)
Labour and the Decolonization Struggle in Trinidad and Tobago incorporates class analyses and assessments of worker affiliation as it relates to organization into occupational categories. There is also consideration of the impact of gender and religion on the working class during the colonial era. This book is an in-depth analysis of the structure and functions of Trinidad and Tobago's early Labour organizations and trade unions and their British and international linkages. The study focuses on the period from the 1920s to 1950 and includes the role of the Trinidad Workingmen's Association (which was later known as the Trinidad Labour Party) in the evolution of working class identity from its rudimentary stages to the subsequent rise of the new trade unionism of the post-1937 era.